Vibration and Noise 2018
DOI: 10.1136/oemed-2018-icohabstracts.1490
|View full text |Cite
|
Sign up to set email alerts
|

850 Occupational health and the social determinants of health: identifying the ethical issues

Abstract: Introduction‘Job security increases health, wellbeing and job satisfaction. Higher rates of unemployment cause more illness and premature death’. Encouraging individuals to be at work can be beneficial, but it also raises questions such as: Do the socially disadvantaged have access to opportunities to improve their health? Do they have fair access to health-enhancing ‘good’ work? OH professionals can have an important influence in matters of health and work, both at ‘front line’ and policy levels. This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Self-motivation was reported as one of the facilitators of employment by the study participants who are employed. Some of our study participants indicated they were not interested in working, and this line of thought is supported by a recent study that suggests that not all persons with disabilities desire to work and should not be pressured to do so (46). Although this seems to support the need for classification of personal factors (as possible barriers and enablers) in the International Classification of Functioning, Disability and Health (ICF) as suggested by Escorpizo and colleagues (47), it may also lead to governments shirking of their responsibility.…”
Section: Discussionsupporting
confidence: 69%
“…Self-motivation was reported as one of the facilitators of employment by the study participants who are employed. Some of our study participants indicated they were not interested in working, and this line of thought is supported by a recent study that suggests that not all persons with disabilities desire to work and should not be pressured to do so (46). Although this seems to support the need for classification of personal factors (as possible barriers and enablers) in the International Classification of Functioning, Disability and Health (ICF) as suggested by Escorpizo and colleagues (47), it may also lead to governments shirking of their responsibility.…”
Section: Discussionsupporting
confidence: 69%